pillars of cognitive training that contribute to the process of developing teaching skills in the subject of observation and application for art education students (Journal of the College of Basic Education, 2023)
The application of the cognitive training strategy in teaching is in order to develop the learners' abilities to use metacognitive skills well, as well as its contribution to facilitating the process of communication between learners well, given that this practical model emphasizes thinking to solve problems and make decisions, as it can be applied in Workshops for training teachers or students to learn within working in groups or in a team style, as they are suitable for training teachers and students who are beginners in the service or continuing in the educational process, so they were applied to a sample of art education students to acquire viewing and application skills, which work to qualify students for the teaching profession in the future, Therefore, he established the problem of his research by raising the following question: What are the pillars of cognitive training that contribute to the process of developing teaching skills in the subject of observation and application for art education students? The current research aims to employ the pillars of cognitive training to develop teaching skills in the subject of observation and application for students of the Department of Art Education.The research community consists of (103) students in the fourth grades in the Department of Art Education / College of Fine Arts - University of Baghdad, who are divided into (4) classes for the academic year 2022-2023.A random sample was selected from the students of the fourth grades / Department of Art Education - the morning study, represented by the two divisions (C-D), totaling (28) students, and they were divided into two groups (T, Z), with (14) students in each group to apply search procedures.To produce the results, the researcher used the SPSS statistical bag, and the most important conclusions are:1- The superiority of the students of the experimental group in their performance of teaching skills within the subject of observation and application is due to their educational commitment to implement the requirements of this subject before and during application.2- It appears that the students of the experimental group gained educational experiences from the courses within the program preparing them for the teaching profession. This was reflected in their presentation of model educational lessons.